Patterns and outcomes of zone 3 REBOA use in the management of severe pelvic fractures: Results from the AAST Aortic Occlusion for Resuscitation in Trauma and Acute Care Surgery database. Issue 4 (8th April 2021) - Harfouche, Melike; Inaba, Kenji; Cannon, Jeremy; Seamon, Mark; Moore, Ernest; Scalea, Thomas; DuBose, Joseph
Abstract : BACKGROUND: Knowledge on practice patterns for aortic occlusion (AO) in the setting of severe pelvic fractures is limited. This study aimed to describe clinical outcomes based on number and types of interventions after zone 3 resuscitative endovascular balloon occlusion of the aorta (REBOA) deployment. METHODS: A retrospective review of the American Association for the Surgery of Trauma Aortic Occlusion for Resuscitation in Trauma and Acute Care Surgery multicenter registry was performed for patients who underwent zone 3 AO from 2013 to 2020. Patients with a blunt mechanism who survived beyond the emergency department were included. Interventions evaluated were preperitoneal pelvic packing (PP), angioembolization (AE), and external fixation (EF) of the pelvis. Management approaches were compared against the primary outcome of mortality. Secondary outcomes included transfusion requirements, overall complications and acute kidney injury (AKI). RESULTS: Of 207 patients who underwent zone 3 AO, 160 (77.3%) fit the inclusion criteria. Sixty (37.5%) underwent AO alone, 50 (31.3%) underwent a second hemostatic intervention, and 49 (30.6%) underwent a third hemostatic intervention. Overall mortality was 37.7% (n = 60). There were no differences in mortality based on any number or combination of interventions. On multivariable regression, only EF was associated with a mortality reduction (odds ratio, 0.22; p = 0.011). Increasing number of interventions were associated with higher transfusion and complication rates. Pelvic packing + AE was associated with increased AKI than PP or AE alone (73.3% vs. 29.5% and 28.6%, p = 0.005), and AE was associated with increased AKI resulting in dialysis than PP alone (17.9% vs. 6.8%, p = 0.036). CONCLUSION: Zone 3 REBOA can be used as a standalone hemorrhage control technique and as an adjunct in the management of severe pelvic fractures. The only additional intervention associated with a mortality reduction was EF. The benefit of increasing number of interventions must be weighed against more harm. Heterogeneity in practice patterns for REBOA use in pelvic fracture management underscores the need for an evidence base to standardize care. LEVEL OF EVIDENCE: Therapeutic, Level IV.